Thermosensitive Chitosan-β-Glycerophosphate Hydrogels as Targeted Drug Delivery Systems: An Overview on Preparation and Their Applications - Pouria Rahmanian-Devin; Vafa Baradaran Rahimi; Vahid Reza Askari (Advances in Pharmacological and Pharmaceutical Sciences)
Today, with the advances in technology and science, more advanced drug delivery formulations are required. One of these new systems is an intelligent hydrogel. These systems are affected by the environment or conditions that become a gel, stay in the circumstance for a certain period, and slowly release the drug. As an advantage, only a lower dose of the drug is required, and it provides less toxicity and minor damage to other tissues. Hydrogels are of different types, including temperature-sensitive, pH-sensitive, ion change-sensitive, and magnetic field-sensitive. In this study, we investigated a kind of temperature-sensitive smart hydrogel, which has a liquid form at room temperature and becomes gel with increasing temperature. Chitosan-β-glycerophosphate hydrogels have been researched and used in many studies. This study investigates the various factors that influence the gelation mechanism, such as gel formation rates, temperature, pH, time, and gel specificity. Hydrogels are used in many drug delivery systems and diseases, including nasal drug delivery, vaginal drug delivery, wound healing, peritoneal adhesion, ophthalmic drug delivery, tissue engineering, and peptide and protein delivery. Overall, the chitosan-β-glycerophosphate hydrogel is a suitable drug carrier for a wide range of drugs. It shows little toxicity to the body, is biodegradable, and is compatible with other organs. This system can be used in different conditions and different medication ways, such as oral, nasal, and injection.